2022
DOI: 10.1155/2022/9417542
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Magnetic Nitrogen-Doped Graphene Oxide Nanocomposite for the Removal of Reactive Orange 12 Dye

Abstract: Herein, we report the nanofabrication of magnetic calcium ferrite (CaFe2O4) with nitrogen-doped graphene oxide (N-GO) via facile ultrasonication method to produce CaFe2O4/N-GO nanocomposite for the potential removal of reactive orange 12 (RO12) dye from aqueous solution. The successful construction of the nanocomposite was confirmed using different characterization techniques including scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform-infrared spectroscopy (FT-IR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Afterwards, a reduction in the removal efficiency occurred until reaching the equilibrium. This reduction is ascribed to the adsorbent reduced surface area due to the adsorbed dye and the adsorbed molecules repulsing with each other [29]. We observed that the nanocomposite of FMWCNT/ V2O5 has the best photocatalytic activity compared with the MWCNT and PMWCNT/V2O5.…”
Section: Effect Of Timementioning
confidence: 83%
“…Afterwards, a reduction in the removal efficiency occurred until reaching the equilibrium. This reduction is ascribed to the adsorbent reduced surface area due to the adsorbed dye and the adsorbed molecules repulsing with each other [29]. We observed that the nanocomposite of FMWCNT/ V2O5 has the best photocatalytic activity compared with the MWCNT and PMWCNT/V2O5.…”
Section: Effect Of Timementioning
confidence: 83%
“…The TEM micrograph of NGO Fig. 4a showed a flaky, smooth, and paper-like structure having a wrinkled morphology with a grain size of 0.26nm 19 . This morphology is due to the stimulation of defects that were introduced during the doping process.…”
Section: Tem Analysismentioning
confidence: 99%
“…Great efforts have been done by scientists to achieve proper methods for dye removal from wastewater. Different methods have been accepted for the removal of organic dyes from water including ion exchange [7], membranes [8,9], adsorption [10][11][12][13][14][15][16][17][18][19], precipitation [20], reverse osmosis [21], coagulation-flocculation [22], ozonation [23,24], electrochemical oxidation [25], and biological treatment [26][27][28]. Among all methods, adsorption is the widely used method for the removal of dyes due to many factors including low cost of processing, high efficiency, fast and easy separation, no secondary pollution, and high recyclability [29,30].…”
Section: Introductionmentioning
confidence: 99%